Summer precipitation for the England and Wales region, 1201–2000 CE, from stable oxygen isotopes in oak tree rings - Loader, NJ; Young, GHF; McCarroll, D; Davies, D; Miles, D; Bronk Ramsey, C (Wiley, 2020)
Oxygen isotope ratios from oak tree rings are used to extend the May–August precipitation totals of the England and Wales precipitation series back to 1201 CE. The agreement between instrumental and reconstructed values is unusually strong, with more than half of the variance explained and standard verification tests passed. The stability of this relationship is confirmed using split‐period calibration and verification. This allows the reconstruction to be variance‐scaled to the full length of the instrumental series back to 1766. Direct comparison with historical reports of very wet and dry summers show good agreement. Near‐constant replication, with a minimum of 10 timbers sourced from historic buildings across central southern England ensures signal strength does not change over time. Summers during the late 20th century appear anomalously dry and those of the 21st century very close to the pre‐20th century average with no evidence in the record of prolonged ‘megadroughts’ across England and Wales.